Natural Self-Foaming Clay Soap with Etlingera elatior Fruit Extract for Skincare - Vica Aspadiah; Wa Ode Sitti Zubaydah; Astrid Indalifiany; Sahidin Sahidin; Adryan Fristiohady; Muhammad Hajrul Malaka; Rahmat Muliadi; Arsyani Parrung (Borneo Journal of Pharmacy)
Etlingera elatior (Wualae), a plant recognized for its flavonoid-derived antioxidant properties, presents a potential source for cosmeceutical applications. This study investigated the formulation and evaluation of a Self-Foaming Clay Soap (SFCS) incorporating an ethanol extract of E. elatior fruit. The SFCS base, comprising surfactant as a cleansing and foaming agent combined with bentonite clay for enhanced serviceability and oil adsorption, was formulated with varying concentrations of bentonite (0%, 5%, 10%, 15%, and 20% w/w), designated as FI to FV, respectively, alongside other necessary excipients. The resulting SFCS preparations underwent rigorous physical and chemical stability assessments following accelerated storage conditions (freeze-thaw cycles). Evaluated parameters included organoleptic properties, foam stability and height, viscosity, dispersibility, homogeneity, and pH. The evaluation revealed that Formulation II (FII), containing 5% w/w bentonite, exhibited the most favorable stability profile and met the established criteria for SFCS semisolid preparations. Specifically, FII demonstrated a foam stabilization rate of 84.61% and a foam height of 2.6 cm after freeze-thaw cycling, a viscosity of 10,000 cPs, a spreadability diameter of 4.1 cm, a homogeneous texture devoid of coarse particles, and a skin-compatible pH of 5. These findings suggest that an SFCS formulation incorporating a 5% w/w concentration of bentonite and E. elatior fruit extract holds promising potential as a stable and efficacious skincare preparation.